Remote Sensing of West Africa's Water Resources Using Multi-Satellites and Models - Ndehedehe, Christopher Edet (Curtin University, 2017)
The preponderance of evidence shows that the warming of the climate system affects natural systems, leading to accelerations in the global hydrological cycle. This thesis discusses hydrological processes and introduces a new multivariate framework to improve drought characterisation/regionalisation in West Africa. Protocols that supports the practical assessment of the influence of global climate and reservoir systems on West Africa’s terrestrial hydrology are outlined. Complementary perspectives on hydrological controls on surface vegetation dynamics are also highlighted.